La participación ciudadana y su impacto en el presupuesto participativo del Gobierno Autónomo Descentralizado del cantón Rocafuerte, período 2019-2022 - Vera Solórzano, Jeniffer Georgina (2025)
The purpose of this research is to analyze citizen participation and its impact on the participatory budget of the Decentralized Autonomous Government in Rocafuerte canton during the period 2019-2022. To this end, three phases were developed in line with the specific objectives set. First, a bibliographic review of the legal and regulatory basis related to the study variables was carried out, using inductive, deductive, analytical-synthetic, quantitative and descriptive methods. Subsequently, both bibliographic and field research types were applied. After that, research techniques were applied such as the interview directed to the head in charge of the corresponding area, the surveys were designed, by carrying out a questionnaire based on the Likert scale and then applied to the citizens. By applying the surveys carried out within the data obtained, they revealed a deficit in citizen participation and in participatory budgeting. Based on these findings, an improvement plan was developed with activities to strengthen and develop both citizen participation and participatory budgeting in Rocafuerte canton. In conclusion, this study highlights the importance of improving and promoting citizen participation and participatory budgeting in Rocafuerte canton. Both elements are essential for development and effective governance within the GAD. Strengthening this area will not only contribute to more inclusive and efficient management, but will also promote greater involvement of citizens and communities in decision-making processes and in the administration of public resources.